E-Service Quality, Product Quality, Application Design, Dan Fulfilment Terhadap Customer Loyalty Melalui Customer Satisfaction Dan Customer Trust Pada Pengguna Shopee - Sulastina Devita, Luh Gede Aan (Universitas Hamzanwadi, 2024)
This research aims to understand what factors influence customer loyalty through customer satisfaction and customer trust in Shopee users, including e-service quality, product quality, application design, and fulfillment. The research population targets all Shopee users, especially those who often shop using the Shopee application. As many as 270 samples were selected using the purposive random sampling method. The use of Google Forms as a data collection medium that can be done online, the results will be processed using SEM-PLS statistical software as a quantitative data analysis procedure. The results of the research where e-service quality, product quality, application design, fulfillment, have a significant influence on customer satisfaction, customer trust, and have an indirect influence through customer loyalty